A BiOBr / UiO-66 heterojunction and its preparation method and application

By preparing BiOBr/UiO-66 heterojunction using PVP and water environment at room temperature, the problem that BiOBr/UiO-66 composites are difficult to retain the UiO-66 octahedral structure is solved, and efficient photocatalytic degradation effect is achieved.

CN116328846BActive Publication Date: 2025-02-14SOUTH CHINA UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310286128.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2025-02-14
Estimated Expiration
2043-03-22

AI Technical Summary

Technical Problem

The existing BiOBr/UiO-66 composite materials are difficult to retain the octahedral structure of UiO-66, resulting in poor catalytic effect.

Method used

The BiOBr/UiO-66 heterojunction was prepared at room temperature using PVP and water environment. The mass ratio of BiOBr to UiO-66 was controlled by ultrasonic stirring and centrifugal washing, and the octahedral structure of UiO-66 was retained.

Benefits of technology

A type II heterojunction with octahedral structure UiO-66 was successfully constructed with a sheet-like BiOBr coated with octahedral structure, which improved the photocatalytic activity and cyclic stability and significantly improved the degradation effect of rhodamine B.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116328846B_ABST
    Figure CN116328846B_ABST
Patent Text Reader

Abstract

The present invention discloses a BiOBr / UiO‑66 heterojunction and a preparation method and application thereof, and belongs to the field of photocatalysis. The BiOBr / UiO‑66 heterojunction is prepared by in-situ growth of BiOBr nanosheets on a carrier UiO‑66 at room temperature. The heterojunction is a type II heterojunction material with a high specific surface area and a strong photocurrent response, which can effectively inhibit the recombination of photogenerated electrons and holes, improve the photocatalytic activity, show good effects in the photocatalytic degradation of rhodamine B, and is suitable for the removal of organic pollutants and the purification of water. The material of the present invention is low in price, simple in preparation process, does not pollute the environment, and has low energy consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysis, and in particular relates to a BiOBr / UiO-66 heterojunction and a preparation method thereof at room temperature and application thereof in photocatalytic degradation of organic pollutants. Background Art

[0002] The continuous development of society has promoted the development of the chemical industry, but in the process of development, industrial wastewater has also been increasing. Dye wastewater is one of the main harmful industrial wastewaters. When dye wastewater is discharged into environmental water bodies, the dyes in the wastewater can absorb light, reduce the transparency of the water body, consume a large amount of oxygen in the water, cause hypoxia in the water body, affect the growth of aquatic organisms and microorganisms, destroy the self-purification of the water body, and cause pollution to natural water bodies. Semiconductor photoreduction is a promising strategy for effectively degrading organic pollutants. Many traditional semiconductors, such as TiO2, ZnO and Cu2O, have been widely used in photocatalytic research. However, their use is limited due to their low degradation performance of pollutants.

[0003] Bismuth oxybromide (BiOBr) consists of [Bi2O2] sheets and dibromine atoms interlaced to form a built-in electric field. It has a unique visible light responsive tetragonal nanosheet structure and indirect transition mode, and the preparation process is simple. Due to its moderate band gap width (its Eg is about 2.9eV) and excellent photoelectric properties, BiOBr exhibits a very high photocatalytic activity. However, BiOBr with a two-dimensional nanosheet structure is prone to agglomeration and has poor dispersion. It has problems such as high recombination rate of photogenerated carriers, small specific surface area, and low visible light utilization.

[0004] MOFs are composed of organic ligands and transition metal ions, and have a large specific surface area and porous structure. In recent years, the construction of various BiOBr@MOFs composite heterojunction materials as a method of modifying BiOBr has overcome the problem of high carrier recombination rate of BiOBr and has been widely studied. Among them, UiO-66, as a Zr-MOF, has a large specific surface area, high stability, and good designability, and has been widely used. However, in the existing research on the composite process of BiOBr / UiO-66, it is difficult to retain the original octahedral structure of UiO-66, and it is impossible to achieve in-situ growth of BiOBr nanosheets on octahedral UiO-66, which makes the BiOBr / UiO-66 composite material unable to retain the octahedral structure of UiO-66 and the catalytic effect is poor. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a BiOBr / UiO-66 heterojunction retaining an octahedral structure, so that it can react at room temperature, reduce the energy consumption of industrial production, and improve the effect of the BiOBr / UiO-66 heterojunction on the degradation of organic dyes.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a BiOBr / UiO-66 heterojunction:

[0008] (1) Synthesis of UiO-66 carrier

[0009] Terephthalic acid is added to N,N-dimethylformamide to obtain solution A, zirconium chloride is added to glacial acetic acid to obtain solution B, solution A and solution B are mixed, ultrasonicated for 10 minutes and stirred for 30 minutes to obtain a transparent solution C, and then the transparent solution C is transferred to a reactor containing a polytetrafluoroethylene liner, and reacted at 100 to 150° C. overnight; after cooling to room temperature, N,N-dimethylformamide and anhydrous ethanol are centrifuged and washed respectively, and the obtained white solid powder is dried in a vacuum oven overnight to obtain a UiO-66 carrier;

[0010] (2) Preparation of BiOBr / UiO-66 heterojunction at room temperature

[0011] PVP (polyvinyl pyrrolidone) was dissolved in pure water and stirred, and then UiO-66 and Bi(NO3)3·5H2O were added, and the suspension was treated with ultrasonic stirring to obtain solution D; KBr was dissolved in pure water to obtain solution E; solution E was added dropwise to solution D, and after ultrasonic stirring for 2 hours, it was centrifuged and washed with deionized water and anhydrous ethanol to obtain a white solid powder, which was vacuum dried overnight.

[0012] Furthermore, step (2) can be carried out at room temperature.

[0013] Furthermore, in step (2), the mass ratio of BiOBr to the BiOBr / UiO-66 heterojunction is controlled to be 0.1 to 0.9.

[0014] Furthermore, in steps (1) and (2), washing is required 2-4 times.

[0015] Furthermore, in step (2), the molar ratio of Bi(NO3)3·5H2O:KBr:UiO-66 is 2-5:2-5:1.

[0016] Furthermore, in step (2), the molar ratio of Bi(NO3)3·5H2O:KBr is 1:1.

[0017] Furthermore, in step (2), the amount of PVP used is: 1 g PVP per millimole of UiO-66.

[0018] Furthermore, in step (2), PVP is dissolved in pure water, and the amount of PVP and pure water used is 100 mL of pure water per gram of PVP.

[0019] Furthermore, in step (2), the volume ratio of pure water in which PVP is dissolved in pure water to pure water in which KBr is dissolved in pure water is 10:15.

[0020] Furthermore, the present invention also provides a BiOBr / UiO-66 heterojunction photocatalytic material prepared by the above-mentioned heterojunction preparation method, which uses lamellar BiOBr to cover octahedral UiO-66 to construct a type II heterojunction.

[0021] The present invention also provides the use of the BiOBr / UiO-66 heterojunction photocatalytic material in decomposing the organic pollutant Rhodamine B under visible light.

[0022] The present invention has the following beneficial effects:

[0023] (1) The present invention uses octahedral UiO-66 as a carrier, which makes the material have higher stability and larger specific surface area. And by introducing BiOBr with a wider light absorption range and band gap structure, a composite heterojunction is successfully constructed. It is beneficial to broaden the light absorption range, improve the light utilization rate, the separation and transmission of photogenerated electrons and holes, and promote the redox reaction of carriers on the semiconductor surface to improve the degradation efficiency.

[0024] (2) The BiOBr / UiO-66 heterojunction has high photocatalytic activity, good cycle stability, and a simple preparation method. By adopting a unique PVP and water environment, it not only reduces the use of organic solvents, but also can achieve the composite of BiOBr / UiO-66 at room temperature, saving costs, easy recycling, and beneficial to environmental improvement.

[0025] (3) At the same time, it is precisely because the present invention adopts a unique PVP and water environment that the BiOBr / UiO-66 heterojunction can retain the octahedral structure of UiO-66 and obtain a better degradation effect of Rhodamine B. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 X-ray diffraction patterns of pure BiOBr, UiO-66 and BiOBr / UiO-66 in Examples 1-3.

[0027] Figure 2 IR spectra of pure BiOBr, UiO-66 and BiOBr / UiO-66 in Example 1.

[0028] Figure 3 3dXPS spectra of Zr of pure UiO-66 and BiOBr / UiO-66 in Example 1.

[0029] Figure 4Bi 4fXPS spectra of pure BiOBr and BiOBr / UiO-66 in Example 1.

[0030] Figure 5 Br 3dXPS spectra of pure BiOBr and BiOBr / UiO-66 in Example 1.

[0031] Figure 6 The full spectrum XPS spectra of pure BiOBr, UiO-66 and BiOBr / UiO-66 in Example 1.

[0032] Figure 7 This is the SEM image of pure BiOBr.

[0033] Figure 8 This is the SEM image of pure UiO-66.

[0034] Fig. 9 This is the SEM image of BiOBr / UiO-66 in Example 1.

[0035] Fig.10 This is the SEM image of the product obtained in Comparative Example 1.

[0036] Fig.11 The SEM image of the product obtained for Comparative Example 2.

[0037] Fig.12 These are the ultraviolet diffuse reflectance spectra of pure BiOBr, UiO-66 and BiOBr / UiO-66 in Example 1.

[0038] Fig.13 The energy band spectra of pure BiOBr, UiO-66 and BiOBr / UiO-66 in Example 1 are shown.

[0039] Fig.14 It is a graph showing the degradation rate of Rhodamine B by pure BiOBr, UiO-66 and BiOBr / UiO-66 in Examples 1-3 under UV-visible light irradiation.

[0040] Fig.15 Graph showing the degradation rate of Rhodamine B of BiOBr / UiO-66 in Example 1 and Comparative Examples 1-2.

[0041] Fig.16 This is the cyclic degradation rate curve of BiOBr / UiO-66 in Example 1 degrading Rhodamine B solution under UV-visible light irradiation. DETAILED DESCRIPTION

[0042] The principles and features of the present invention are described below in conjunction with the examples, which are only used to explain the present invention and are not intended to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0043] The specific preparation method of UiO-66 of the present invention is:

[0044] Preparation of UiO-66: 1 mmol of terephthalic acid (0.166 g) was added to 45 mL of N, N-dimethylformamide (DMF), 1 mmol of zirconium chloride (0.158 g) was added to 5 mL of glacial acetic acid (to adjust the morphology of UiO-66), and the two solutions were mixed and ultrasonicated for 10 minutes and stirred for 30 minutes. The transparent solution was then transferred to a reactor containing a polytetrafluoroethylene liner and reacted at 120°C for 24 hours. After cooling to room temperature, it was centrifuged and washed three times with N, N-dimethylformamide (DMF) and anhydrous ethanol. The obtained white solid powder was dried in a vacuum oven at 60°C overnight to obtain the UiO-66 carrier.

[0045] Embodiment 1:

[0046] 0.1g PVP was dissolved in 10mL pure water, stirred for 10 minutes, then 0.1mmol (0.0657g) UiO-66 and 0.3232mmol (0.1567g) Bi(NO3)3·5H2O were added, and ultrasonic stirring was performed for 1-2h to obtain solution D; 0.3232mmol (0.03846g) KBr was dissolved in 15mL pure water to obtain solution E; solution E was added dropwise to solution D, and ultrasonic stirring was performed for 1-2 hours. Washed by centrifugation with deionized water and anhydrous ethanol. The powder was dried in a vacuum oven overnight. The white solid obtained at last was 60% BiOBr / UiO-66.

[0047] Embodiment 2:

[0048] 0.15g PVP was dissolved in 15mL pure water, stirred for 10 minutes, then 0.1mmol (0.0657g) UiO-66 and 0.2154mmol (0.1045g) Bi(NO3)3·5H2O were added, and the suspension was treated with ultrasonic stirring for 1-2h to obtain solution D; 0.2154mmol (0.02564g) KBr was dissolved in 15mL pure water to obtain solution E; solution E was added dropwise to solution D, and ultrasonic stirring was treated for 1-2h. Washed by centrifugation with deionized water and anhydrous ethanol. The powder was dried in a vacuum oven overnight. The white solid obtained at last was 50% BiOBr / UiO-66.

[0049] Embodiment 3:

[0050] Dissolve 0.15g PVP in 15mL pure water, stir for 10 minutes, then add 0.1mmol (0.0657g) UiO-66 and 0.5028mmol (0.2438g) Bi(NO3)3·5H2O, and treat the suspension with ultrasonic stirring for 1-2h as D solution; dissolve 0.5028mmol (0.05983g) KBr in 15mL pure water as E solution; add E solution dropwise into D solution, and treat with ultrasonic stirring for 1-2h. Wash with deionized water and anhydrous ethanol by centrifugation. Dry the powder in a vacuum oven overnight. The white solid obtained at last is 70% BiOBr / UiO-66.

[0051] Comparative Example 1:

[0052] 0.1g PVP was dissolved in 10mL pure water, stirred for 10 minutes, and then 0.1mmol (0.0657g) UiO-66 and 0.3232mmol (0.1567g) Bi (NO3) 3 · 5H2O were added to obtain solution D; 0.3232mmol (0.03846g) KBr was dissolved in 15mL pure water to obtain solution E; solution E was added dropwise to solution D, stirred for 10 minutes, placed in a reactor with a polytetrafluoroethylene liner, and reacted at 120°C for 2h. Washed by centrifugation with deionized water and anhydrous ethanol. The powder was dried in a vacuum oven overnight. The white solid obtained at last was 60% BiOBr / UiO-66 under PVP + water + hydrothermal conditions.

[0053] Comparative Example 2:

[0054] 0.1mmol (0.0657g) UiO-66 and 0.3232mmol (0.1567g) Bi(NO3)3·5H2O were added to 10mL ethylene glycol, stirred for 10 minutes, and the suspension was subjected to ultrasonic stirring for 1-2h to obtain solution D; 0.3232mmol (0.03846g) KBr was dissolved in 15mL ethylene glycol to obtain solution E; solution E was added dropwise to solution D, and ultrasonic stirring was carried out for 1-2h. Washed by centrifugation with deionized water and anhydrous ethanol. The powder was dried in a vacuum oven overnight. The white solid obtained at last was 60% BiOBr / UiO-66 under ethylene glycol + room temperature conditions.

[0055] Test and results: The method for investigating the photocatalytic activity of the material provided by the present invention comprises the following steps:

[0056] Step 1: Disperse 15 mg of heterojunction photocatalytic material into 100 mL of 10 mg / L Rhodamine B aqueous solution at room temperature, stir magnetically for a certain period of time in a dark environment, and after reaching adsorption-desorption equilibrium, turn on the xenon lamp light source and irradiate with ultraviolet-visible light;

[0057] Step 2: Take out 5 mL of the suspension, centrifuge and remove the supernatant;

[0058] Step 3: Use a UV-visible spectrophotometer to measure the absorbance of the Rhodamine B solution at a wavelength of 554 nm. According to the Beer-Lambert law, the concentration of the Rhodamine B solution can be calculated from the measured absorbance.

[0059] Table 1

[0060]

[0061] The degradation rates and kinetic constants of the embodiments of the present invention and the comparative examples are shown in Table 1. Fig.13 Combined with the pseudo-first-order kinetic model, the k value of 60% BiOBr / UiO-66 was calculated to be 0.03522min -1 , is the k value of pure BiOBr sample (0.01238min -1 ) is 2.9 times that of the UiO-66 sample (0.00035min -1 ) times.

[0062] Figure 1 The XRD patterns of catalysts BiOBr, UiO-66, and BiOBr / UiO-66 at 2θ angles of 5-80° are shown. The peaks at 2θ angles of 7.4° and 8.5° correspond to the UiO-66 (110) and (200) crystal planes. The peaks at 31.6° and 32.2° correspond to the BiOBr (102) and (110) crystal planes. In the BiOBr / UiO-66 composite catalyst, the above peaks all exist, and as the BiOBr content increases, the intensity of the characteristic diffraction peak of UiO-66 decreases, indicating that the BiOBr / UiO-66 composite material with UiO-66 as the carrier was successfully synthesized.

[0063] Figure 2 This is the infrared spectrum of 60% BiOBr / UiO-66 obtained in Example 1. In the infrared spectrum of pure BiOBr, 525 cm -1 The peaks at 1579 and 1390 cm-1 are the Bi-O stretching vibration peaks. -1 Strong asymmetric stretching vibration peaks of O=CO and symmetric stretching peaks appear everywhere. -1 is the carboxyl peak, 1506cm -1 The weak peak at 751cm is the C=C bending vibration peak on the benzene ring. -1 and 654cm -1 The OH and CH of the ligand H2BDC and the bending vibration of Zr-O appear at 1100 cm -1It can be seen that as BiOBr is attached to UiO-66, the main structure is not changed.

[0064] Figure 3 Figure 2 is the Zr 3d XPS spectra of UiO-66 and BiOBr / UiO-66 in Example 1. The spectrum peaks of BiOBr / UiO-66 have three Zr 3d orbital peaks of UiO-66 monomer, proving that BiOBr / UiO-66 contains UiO-66.

[0065] Figure 4 , 5 4fBr 3d XPS spectra of BiOBr and BiOBr / UiO-66 of Example 1. The BiOBr / UiO-66 composite material shows Bi 4f and Br 3d characteristic peaks of BiOBr monomer, indicating that BiOBr / UiO-66 contains BiOBr.

[0066] Figure 6 The full XPS spectrum (a), Zr 3d (b), Bi 4f (e) and Br 3d (f) of BiOBr / UiO-66 obtained in Example 1. It can be seen from the figure that the composite catalyst BiOBr / UiO-66 has two monomeric peaks of Bi, Br and Zr, which further indicates that the composite is successful. The positions of these peaks are all offset, indicating that the formation of the heterojunction changes the electron transmission path, further causing the electron binding energy peak to shift.

[0067] Figure 7 This is a SEM image of pure BiOBr. It can be seen that BiOBr is a smooth nanosheet with a width of 100-200nm and a thickness of about 50nm, and the nanosheets are stacked on each other.

[0068] Figure 8 This is the SEM image of pure UiO-66. It can be seen that the monomer UiO-66 is an octahedral structure with a diameter of about 500nm.

[0069] Fig. 9 This is the SEM image of 60% BiOBr / UiO-66 obtained in Example 1. It can be seen that the carrier UiO-66 still maintains an octahedral morphology, and the BiOBr nanosheets are attached to the octahedral structure of UiO-66.

[0070] Fig.10 and Fig.11 The SEM images of 60% BiOBr / UiO-66 obtained in Comparative Example 1 and Comparative Example 2 respectively show that the carrier UiO-66 has lost its octahedral morphology.

[0071] Fig.12 and Fig.13The UV diffuse reflectance spectra and energy band spectra of the composite material and monomer obtained in Example 1 show that due to the presence of BiOBr, the light absorption range of 60% BiOBr / UiO-66 is broadened and the cutoff wavelength is increased compared with UiO-66. According to the Kubelka-Munk law, αhν=A(hν-Eg) 1 / 2 (where α, h, and ν are absorbance, Planck constant, and light frequency, respectively; A is a proportionality constant; Eg is the band gap and HOMO-LUMO energy gap) It is inferred that the HOMO-LUMO energy gap of UiO-66 is 3.88 eV, and the band gap of BiOBr is 2.91 eV.

[0072] Fig.14 The degradation rate of BiOBr, UiO-66 and other composite materials with different proportions under UV-visible light irradiation is shown in the figure. After 70 minutes of illumination, pure UiO-66 only degraded 3.14% of Rhodamine B, which was not a good effect. BiOBr degraded 55.9%. However, after constructing a heterojunction with UiO-66, the degradation efficiency of the composite catalyst was greatly improved. When the optimal loading was 60%, BiOBr / UiO-66 could degrade 94.9% of Rhodamine B.

[0073] Fig.15 The degradation rate of 60% BiOBr / UiO-66 obtained in Example 1 and Comparative Examples 1 and 2 under UV-visible light irradiation is shown in the figure. After 70 minutes of irradiation, the 60% BiOBr / UiO-66 prepared in Comparative Example 1 (under PVP+H2O+hydrothermal conditions) can be degraded to 88.4%, and the 60% BiOBr / UiO-66 prepared in Comparative Example 2 (under ethylene glycol+room temperature conditions) can be degraded to 76.4%, both of which are lower than the degradation level of Example 1 of the present application.

[0074] Fig.16 The degradation rate curve of the 60% BiOBr / UiO-66 obtained in Example 1 under UV-visible light irradiation is shown. After each cycle, the catalyst was washed three times with deionized water and anhydrous ethanol. After three cycles, the degradation rate of Rhodamine B dropped from 94.9% to 89.2%, and the catalyst still maintained a high catalytic activity.

[0075] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for preparing a BiOBr / UiO-66 heterojunction photocatalytic material, characterized in that: The steps include: (1) Synthesis of UiO-66 carrier 1 mmol of terephthalic acid was added to 45 mL of N, N-dimethylformamide, and 1 mmol of zirconium chloride was added to 5 mL of glacial acetic acid. The two solutions were mixed and ultrasonicated for 10 minutes and stirred for 30 minutes. Then, the mixture was transferred to a reactor containing a polytetrafluoroethylene liner and reacted at 120°C for 24 hours. After cooling to room temperature, the mixture was centrifuged and washed three times with N, N-dimethylformamide and anhydrous ethanol respectively. The obtained white solid powder was dried in a vacuum oven at 60°C overnight to obtain a UiO-66 carrier. (2) Preparation of BiOBr / UiO-66 heterojunction at room temperature 0.1 g PVP was dissolved in 10 mL pure water and stirred for 10 minutes. Then 0.1 mmol UiO-66 and 0.3232 mmol Bi(NO3)3·5H2O were added and ultrasonically stirred for 1-2 h to obtain solution D. 0.3232 mmol KBr was dissolved in 15 mL pure water to obtain solution E. Solution E was added dropwise into solution D and ultrasonically stirred for 1-2 hours. The solution was washed by centrifugation with deionized water and anhydrous ethanol. The powder was dried in a vacuum oven overnight. The white solid obtained was 60% BiOBr / UiO-66.

2. The BiOBr / UiO-66 heterojunction photocatalytic material prepared by the preparation method according to claim 1.

3. The use of the BiOBr / UiO-66 heterojunction photocatalytic material according to claim 2, characterized in that: Used to decompose Rhodamine B under visible light.

Citation Information

Patent Citations

  • BiOBr and MOF material composite photocatalyst, preparation method and application thereof

    CN111939979A